2020
DOI: 10.2473/journalofmmij.136.14
|View full text |Cite
|
Sign up to set email alerts
|

銅の電解精製とアノード不動態化

Abstract: In the process of electrorefining of copper, application of higher current density increases the tendency of anode passivation. The passivation disrupts the sound operation of the electrorefining process, reducing the current efficiency and the quality of copper deposited on the cathode. Therefore, anode passivation should be avoided in industrial electrolytic cells. Anode passivation is attributed to the precipitation of copper sulfate, which is saturated locally in the vicinity of the anode surface. When a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…As a result of this situation, the concentration of impurities included in crude Cu produced by pyrometallurgy has been increasing. 1,2) Electrorefining of crude Cu obtained by pyrometallurgy produces Cu with a purity of above 99.99 mass%, which is used for electrical wire and rolled products. The anode for this electrorefining is usually crude Cu with a purity above 99 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this situation, the concentration of impurities included in crude Cu produced by pyrometallurgy has been increasing. 1,2) Electrorefining of crude Cu obtained by pyrometallurgy produces Cu with a purity of above 99.99 mass%, which is used for electrical wire and rolled products. The anode for this electrorefining is usually crude Cu with a purity above 99 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…Their average compositions (Table 1(a)) were similar to that of black-copper in industrial use. 3,33,34) For comparison, a Cu alloy block (10 mm © 10 mm © 5 mm, 4.00 g) with the same composition as the shot samples, and a Ag-free Cu alloy in the same shot form (Table 1(b)) were also used. The average compositions and variations were determined four times for three shot samples by chemical analysis, i.e., dissolution in aqua regia and then inductively coupled plasma atomic emission spectroscopy (Spectro Arcos, Spectro Analytical Instruments, Kleve, Germany) measurements.…”
Section: Methodsmentioning
confidence: 99%
“…This passivation makes treatment of black-copper anodes via conventional processes difficult. 3,4) Among impurity elements, Ag significantly promotes anode passivation. The Ag contents of crude copper is carefully controlled at 10 750 ppm, 5) and it has been reported that crude copper anodes containing Ag at 2600 ppm hardly work because of passivation.…”
Section: Introductionmentioning
confidence: 99%